Effect of Caffeine on the Repeated Modiﬁed Agility Test from some Cardiovascular Factors, Blood Glucose and Rating of Perceived Exertion in Young People - Nidhal JEBABLI; Nejmeddine OUERGHI; Jihen BOUABID; Ramzi BETTAIB (Tehran University of Medical Sciences, 2017)
Background: The aim of this study was to compare the effects of the ingestion of either the caffeine (CAF) or the placebo (PLA) on performance of repeated modiﬁed agility test (RMAT), some cardiovascular factors, metabolic and notes of perceived exertion (RPE) in young males and females. Methods: In a randomized double-blind study, we enrolled 18 active students (10 males and 8 females) in Sport Sciences pursuing degrees in Exercise Science and Physical Education at the University of Sports of Kef (Tunisia), during the academic year 2013-2014. All participants were ingested CAF (5 mg.kg-1) or PLA 60 min before performing an RMAT. Total times (TT), peak time (PT) and fatigue index (FI) were identified as the RMAT indices. Heart rate (HR), arterial pressures (PA), blood glucose (BG) and RPE were assessed before, during and after the RMAT. Results: Taking caffeine had been improved the performance by the significant decreased of TT on male gender better than female gender and the entire group. In addition, there was a significant improvement on HR during and after RMAT in both genders and the whole group, except after RMAT among male gender. However, the repeated measurement results had demonstrated no effect of caffeine on PA, BG and RPE. Conclusion: Caffeine supplement had a beneficial effect on agility performance and HR in male better than in female, although, there was no improvement in PA, BG and RPE.